Influence Of Workload And Job Satisfaction Of Pharmaceutical Workers On The Achievement Of Quality Indicators With Motivation As Intervening Variables In Jakarta Dharmais Cancer Hospital - Gina Fadhilah; Kemala Rita Wahidi; Endang Ruswanti (Syntax Corporation Indonesia, 2022)
Based on an initial survey of 10 pharmacists, there are still many employees (10%) who complain of being tired when the office, especially the morning service, sometimes doesn't have time to rest, eat, plus pharmacists who don't come because of illness, causing the workload to be more The survey results also showed 50% of employees expressed job dissatisfaction this was related to salary provision, relationships with superiors and job placements were not in accordance with their skills and abilities. In addition, 20% of employees show low work motivation, this is because the work environment is not conducive and the workload is high. In addition to the results of observations based on the RSKD suggestion box, the phenomenon of complaints felt by 3 patients / families, including